Primary pulmonary synovial sarcoma: a case report - Liu, Junfeng (Int J Clin Exp Pathol, 2018)
Primary pulmonary synovial sarcoma (PPSS) is a relatively rare mesenchymal tumor accounting for 0.5% of all primary lung malignancy with a highly progressive potential. We describe a case of a 52-year-old man whose chest CT-imaging revealed a heterogeneous mass (8.5 × 7.7 × 6.5 cm), with multiple nearly-circular nodules in bilateral pulmonary tissues. EBUS-TBNA and pathological H&E and immunohistochemical examination were performed subsequently, and sarcoma was suspected. Then molecular detection was used and PPSS was confirmed by the detection of the expression of SYT gene (positive) and EWSR1 gene (negative) in situ hybridization. This report shows that EBUS-TBNA combined with in situ hybridization could serve as a helpful diagnostic tool.